2014
DOI: 10.1364/boe.5.003949
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of ablative fractional laser-assisted drug delivery with optical coherence tomography

Abstract: Abstract:Fractional resurfacing creates hundreds of microscopic wounds in the skin without injuring surrounding tissue. This technique allows rapid wound healing owing to small injury regions, and has been proven as an effective method for repairing photodamaged skin. Recently, ablative fractional laser (AFL) treatment has been demonstrated to facilitate topical drug delivery into skin. However, induced fractional photothermolysis depends on several parameters, such as incident angle, exposure energy, and spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…An earlier study demonstrated proofof-concept with four different lasers [14] and this has been followed up with further work using millisecond-pulsed CO 2 lasers. In one case, nails were imaged post-poration with optical coherence tomography; in another, application of a topical cream to porated nails produced a positive treatment effect in nearly all patients [15,16]. However, exposure to laser ablation was not without noticeable pain, probably because the long pulse duration caused local heating.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study demonstrated proofof-concept with four different lasers [14] and this has been followed up with further work using millisecond-pulsed CO 2 lasers. In one case, nails were imaged post-poration with optical coherence tomography; in another, application of a topical cream to porated nails produced a positive treatment effect in nearly all patients [15,16]. However, exposure to laser ablation was not without noticeable pain, probably because the long pulse duration caused local heating.…”
Section: Introductionmentioning
confidence: 99%
“…The setup of the SS-OCT system is similar to that of a previous study [42]. A swept source (HSL-20, Santec Corp., Aichi, Japan) at 1.3 μm was used as the light source of the OCT system with a scanning spectrum of 110 nm.…”
Section: Experiments Methods and Setupmentioning
confidence: 99%
“…In previous studies, we have demonstrated that the photothermolysis of human skin induced by an ablative laser can be monitored with OCT [41]. Furthermore, preliminary OCT results have proven the feasibility of laser-assisted therapy [42]. In this study, we investigate the time-dependent variation of OCT intensity during the diffusion process of drug particles.…”
Section: Introductionmentioning
confidence: 99%
“…[80][81][82][83][84][85][86] OCT is able to visualize the nail plate, nail bed, and nail matrix, 87 and the method has been using for assessing effectiveness of transnail drug delivery using ablative fractional laser with OCT, suggesting the technology to be an effective tool for monitoring both depth of laser penetration and drug delivery efficacy in nails. 80,81 Measurement of nail thickness with OCT has been applied, showing lower degrees of variation compared to ultrasonography, 87 though lacking the ability to visualize single cellular structures compared to confocal laser scanning microscopy. 88 A "demonstration of principle" study to assist the planning of follicular unit extraction with OCT has been made in order to easily evaluate the angles of hair follicles during hair transplants.…”
Section: Physiological Studiesmentioning
confidence: 99%